A brief review of the clinical anatomy of the vestibular-ocular connections—how much do we know? - Bronstein, A M (Eye (Lond), 2015)
The basic connectivity from the vestibular labyrinth to the eye muscles (vestibular ocular reflex, VOR) has been elucidated in the past decade, and we summarise this in graphic format. We also review the concept of ‘velocity storage', a brainstem integrator that prolongs vestibular responses. Finally, we present new discoveries of how complex visual stimuli, such as binocular rivalry, influence VOR processing. In contrast to the basic brainstem circuits, cortical vestibular circuits are far from being understood, but parietal-vestibular nuclei projections are likely to be involved.